2015
DOI: 10.18632/oncotarget.5655
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of nitroxoline as a potential anticancer agent against human prostate cancer - a crucial role on AMPK/mTOR signaling pathway and the interplay with Chk2 activation

Abstract: Nitroxoline is an antibiotic by chelating Zn2+ and Fe2+ from biofilm matrix. In this study, nitroxoline induced G1 arrest of cell cycle and subsequent apoptosis in prostate cancer cells through ion chelating-independent pathway. It decreased protein levels of cyclin D1, Cdc25A and phosphorylated Rb, but activated AMP-activated protein kinase (AMPK), a cellular energy sensor and signal transducer, leading to inhibition of downstream mTOR-p70S6K signaling. Knockdown of AMPKα significantly rescued nitroxoline-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
39
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 50 publications
7
39
0
2
Order By: Relevance
“…AMPK/mTOR pathway is known as a common signaling pathway associated with tumors (An et al, ; C. Cao et al, ). It mainly takes part in the progression of proliferation and autophagy (An et al, ; Chang, Hsu, Leu, Chen, & Guh, ; H. Tang et al, ). AMPK/mTOR pathway had been reported to suppress progression in breast cancer (Ren, Ren, Cheng, & Xu, ) and participated in promoting autophagy in B251 cells (Wang, Zhang, Luo, Ning, & Fang, ).…”
Section: Discussionmentioning
confidence: 99%
“…AMPK/mTOR pathway is known as a common signaling pathway associated with tumors (An et al, ; C. Cao et al, ). It mainly takes part in the progression of proliferation and autophagy (An et al, ; Chang, Hsu, Leu, Chen, & Guh, ; H. Tang et al, ). AMPK/mTOR pathway had been reported to suppress progression in breast cancer (Ren, Ren, Cheng, & Xu, ) and participated in promoting autophagy in B251 cells (Wang, Zhang, Luo, Ning, & Fang, ).…”
Section: Discussionmentioning
confidence: 99%
“…In that study, nitroxoline was found to affect viability, to drastically reduce clonogenic activity, to hamper cell cycle and to promote apoptosis in pancreatic cancer cell lines, both as a single agent and in combinations with other drugs 7 . In addition to pancreatic cancer, this drug affects viability and growth of cell lines representative of other tumors, including neuroblastoma, glioma, myeloma, prostate, lung, kidney and bladder cancers [8][9][10][11][12][13][14][15][16][17][18][19] . Remarkably, this antibiotic is also effective in several cancer xenograft and genetically engineered mice models [8][9][10]12,14,15,18 .…”
mentioning
confidence: 99%
“…Nitroxoline is an antibiotic widely used in several countries from 1960s and is able to chelate divalent metal ions such as Mg 2+ and Mn 2+ , an activity which is considered as a possible mechanism for its antibacterial action 3 . To analyze mechanisms by which this antibacterial exerts its anticancer activity, several studies screened for specific candidate targets and molecular pathways known to play an important role in cancer biology [7][8][9][10][11][12][13][14][15][16][17][18][19] . Using this approach, disparate targets have been proposed to be responsible for nitroxoline anticancer effects.…”
mentioning
confidence: 99%
“…The effect of nitroxoline on cell-cycle arrest and apoptosis was also confirmed in prostate cancer cells (Chang et al, 2015). Nitroxoline induced G1 cell-cycle arrest on both hormone-sensitive and hormone-refractory prostate cancers.…”
Section: Antitumor Activity Of Nitroxolinementioning
confidence: 64%
“…It is crucial for cell proliferation, growth, survival and metabolism, and effects G1 cell-cycle arrest via the cyclin D1-Rb-Cdc25A axis. Moreover, nitroxoline contributes to cell apoptosis by inducing AMPK dependent activation of Chk2 that encodes a serine/threonine kinase that coordinates cell responses to DNA damage (Chang et al, 2015). On the other hand, through the AMPK pathway, nitroxoline also induces autophagy, resulting in a decreased effect on apoptosis (Chang et al, 2015).…”
Section: Antitumor Activity Of Nitroxolinementioning
confidence: 99%